The Effect of The Problem-Based Learning Model Assisted by Wordwall Media on Students’ Activeness in Indonesian Language Learning - Kawanti, Julia; Mardiana, Mardiana (LPPM Universitas Jambi, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Wordwall media on the learning activeness and learning outcomes of third-grade students at SD Negeri 28 Kelakik. The research employed a quantitative approach with a pre-experimental design using a one-group Pretest-Posttest design. The sample consisted of 20 students selected through total sampling technique. The research instruments included multiple-choice tests, observation sheets of student activeness, interviews, and documentation. Data analysis was conducted using normality test, paired sample t-test, and N-Gain analysis. The results showed that the data were normally distributed, and there was a significant effect of the PBL model assisted by Wordwall on learning outcomes (Sig. 0.000 < 0.05). The N-Gain value was categorized as moderate (0.63). The average student score increased from 58 to 84. Therefore, it can be concluded that the PBL model assisted by Wordwall is effective in improving students’ activeness and learning outcomes.